Commodification of Intimacy within the Post-Soviet Space: A Case of Compensated Dating in Russia, Ukraine, and Belarus - СуторминаАлёна Евгеньевна; SwaderChristopher S.; БуничЕкатерина Александровна; СтрелковаОльга Владимировна (Journal of Economic Sociology, 2011)
Detailed description in the text